Pengaruh Intensitas Aset Tetap, Insentif Eksekutif dan Corporate Risk terhadap Tax Avoidance pada Perusahaan - Farina Jessen Yap; Rudyanto Simanjuntak (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
Taxes represent a genuine social contribution that supports a nation's revenue growth. In practice, governments face numerous challenges in maximizing tax collections, one of which involves tax avoidance. This study aims to examine and assess how fixed asset intensity, executive incentives, and corporate risk influence tax avoidance in companies. The research employs a quantitative method, utilizing documentation and literature reviews for data collection. Multiple linear regression and classical assumption tests are applied to analyze the data quality and relationships among variables. The findings reveal that fixed asset intensity, executive incentives, and corporate risk collectively impact corporate tax avoidance. Individually, fixed asset intensity negatively and significantly affects tax avoidance, whereas executive incentives and corporate risk exhibit positive and significant influences. The study concludes that these three factors significantly influence tax avoidance in companies, with the remaining 9.2% of variability explained by other factors such as leverage, profitability, and corporate governance practices.